Review of the Chilean Shipping Industry: Challenges to Achieving Emissions Reductions by 2030, 2050, and Beyond by Applying Alternative Fuels - Joel R. Pérez Osses; Carlos A. Reusser (Atmosphere)
Alternative fuels are a measure discussed in the International Maritime Organization (IMO) strategy in order to reduce emissions from shipping. This is deemed necessary to achieve emissions reduction in the shipping industry, but the way in which this needs to be applied to such a resilient industry overall is a current challenge. The increasing impact of ships’ emissions on the environment and current preventative regulations that have been introduced by the IMO present a paradigm in the consideration of alternative fuel measures that could possibly be applied to this industry. Existing and new ships are different assets that need to converge to reduce emissions partially or completely by 2030. Determining the technology readiness level (TRL) for producing these alternative fuels, and their availability to be applied to these assets, involves a mix of evaluation and analysis as covered in this work. The TRL of producing alternative fuels is at the commercial level, which means that the shipping industry could apply it by itself following economical evaluation, but these alternative fuels’ services and capabilities have not yet been evaluated in comparison to traditional fuels. A supply chain for alternative fuel production needs to be built to serve the shipping industry. This supply chain would need the support of governments because the inclusion of alternative fuels in the supply chain would impact the national energy matrix. This work presents a revised path for the Chilean shipping industry to follow, focusing on the consideration not only of the emission reduction measures themselves but also of the analysis of the impact of those measures on the supply chains, as well as the stringent necessary regulations issued by the IMO and the government. The methodology used in this review considers the revision of the actual advances towards emission reductions, the development of alternative fuels, and the possibilities of applying them, considering the current state of development of the Chilean shipping industry. This review shows that room for the development of the Chilean shipping industry exists if it wants to move towards using alternative fuels with support from the government.